Oxidative Stress in Fish Cyprinus Carpio Caused By Oxytetracycline - M, Sharma; P, Daundkar; D, Rani (Asian Journal of Pharmaceutical Research and Development, 2021)
Environment pollution is posing threat to humans and animals. Environmental pollution is caused by anthropogenic activities and is a major problem in many countries. The present study was investigated to find the oxidative stress induced by oxytetracycline in fish Cyprinus carpio. The acute exposure was given for 24, 48, 72 and 96 hrs of exposure. The sublethal concentration decided was 80 mg/l. Under oxidative stress, parameters such as glutathione-S-transferase (GST), catalase (CAT) and superoxide dismutase (SOD) were studied and a significant reduction in the activity of GST, CAT and SOD was observed in the treated group as compared to control. A significant decrease in SOD and CAT is at 72 and 96 hours of exposure while, a significant decline trend after 24 hours of exposure in GST activity was observed. Acute exposure of OTC enhanced reactive oxygen species formation and inhibited antioxidant capacities in the fish. Based on the results it is evident that oxytetracycline is causing oxidative stress in fish. It is also demonstrated that oxidative stress biomarker may play important in biomonitoring assessment protocol.